Co-production of biofuels and value-added compounds from industrial Eucalyptus globulus bark residues using hydrothermal treatment - Gomes, Daniel Gonçalves (2021)
In this work, hydrothermal treatment was assessed for the fractionation of industrial Eucalyptus globulus bark residue (EBR) to obtain biofuels and value-added compounds (such as oligosaccharides and phenolic compounds) in separated streams. Hydrothermal treatment was evaluated under non-isothermal regimen in the range of maximum temperature (Tmax) of 177228 °C or severities (S0) between 2.76 and 4.25. The highest oligosaccharides concentration (17.5 g/L) was achieved at S0 of 3.69, corresponding to hemicellulose recovery of 77.30%. Under all severities evaluated in this work, over 90.94% and 84.17% of cellulose and lignin remained in the solid phase, respectively. The increase of S0 improved 4.38-fold the enzymatic saccharification of cellulose, the highest glucose yield (84%) being achieved at S0 of 4.04. Considering the maximal recovery of polysaccharides as glucose and oligosaccharides from the liquid and solid phases, S0 of 4.04 was selected for bioethanol production using high solid loadings and following different strategies (simultaneous saccharification and fermentation SSF and pre-saccharification and simultaneous saccharification and fermentation PSSF). The utilization of 15% hydrothermally pretreated EBR without nutrient supplementation resulted in 26 g/L of ethanol, independently of the strategy used. An increase up to 17.5% solids and employing nutrient supplementation enabled the production of 38 g/L (or 4.8% v/v) of ethanol by PSSF.